DIVERSITY AND INTRAGROUP CONFLICT AT WORK: AN EMPIRICAL STUDY IN PORTUGAL - da França, Carine Bastos (2010)
Facing a constantly changing environment, nowadays’ organizations are looking for innovative ways of organizing and managing work, in which workgroups represent a source of competitive advantage. In this context, group diversity has received increasingly attention by researchers. Jackson, May and Whitney (1995) define diversity in terms of characteristics classified as observable or underlying, as either task-related or relational-oriented. Although there are no conclusive results on this subject, researches relating diversity and the main types of conflict (affective and task-related) suggest that relational-oriented diversity (e.g., age, gender) influences the emergence of affective conflict, while task-oriented diversity (e.g., education, organizational tenure) contributes to task conflict (PELLED, 1996; JEHN; NORTHCRAFT; NEALE, 1999; PELLED; EISENHARDT; XIN, 1999). Following Jackson et al. (1995), we analyzed the effects of observable attributes of diversity (educational level, gender and age), on the emergence of intragroup conflict in 231 Portuguese workgroups, whose members perceived themselves as a group, and interacted with interdependence to achieve common goals. The Intragroup Conflict Assessment Scale (DIMAS; MIGUEZ; LOURENÇO, 2007) and a sociodemographic questionnaire were used. In contrast with the literature, but congruent with recent Portuguese researches (PASSOS, 2005; SILVESTRE, 2008), our results revealed no association between the studied diversity variables and intragroup conflict, indicating new directions in this field, and highlighting the importance of considering different contexts and variables in diversity’s studies.